(untitled) (Veterinary Science, 2018)
The warranty level of ether extract, gross protein and phosphorus of five dogs and three cats’ commercial food labels were analysed. Ether extract, gross protein and phosphorous were determined by direct intermittent extract means of soxhlet, Kjeldahl and colourimetric by reduction of sulphur-molybdate respectively. Each determination was repeated three times and the mean value obtained was expressed as a percentage of dry matter, thereafter, the obtained values were compared with those informed by the manufacturer. The ether extract values determined of five dogs and two cat food was lower than those expressed in the label. The phosphorous value was lower in two dog food, and the level of gross protein was lower in four dogs and one cat food in relation to the label data. Just one dog food showed values of ether extract higher than those expressed in the label. The content of moisture was determined by the indirect gravimetric method, desiccating the sample at 65 °C for 48 hours, and observing values of 46.6%, lower than those informed by the label. It concluded that all dog food had incoherency in at least one of the parameter studied with respect to the information presented in the manufacturer label. In relation to the cat food just one fulfils the values informed in the manufacturer label. Finally, it was stunned the low level of moisture found in all pet food analysed.